Effect of Tetronasin on frothy bloat in cattle caused by high-grain diet - Neibarger, L.R.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feeding Tetronasin reduced incidence of frothy bloat in cattle fed a high-grain diet. The effective dose was 0.25 mg/kg body weight when administered prior to the onset of frothy bloat. At 0.15 mg/kg body weight, the antibiotic was less effective but the degree of bloat was considerably less than that of steers fed no antibiotic. Tetronasin also reduced the severity of bloat in steers that were already bloating prior to its administration.
Keywords: Beef; Tetronasin; Bloat; High-grain diet